Feasibility of developing children's Pill School within a UK hospital. Issue 7 (23rd November 2020) - Rashed, Asia N; Terry, David; Fox, Andy; Christiansen, Nanna; Tomlin, Stephen
Abstract : Objective: We assessed the feasibility of introducing an intervention (children's Pill School—PS) within a UK hospital to provide swallowing training for children, identified the proportion of children who can be switched from oral liquid medicines to pills and assessed children/parents' opinions about the PS training. Methods: 30 inpatient children (aged 3–18 years; taking oral liquid medicines; their liquid medications assessed suitable for switching to pills; can (and their parents) speak/understand English were included. Training sessions were delivered using hard sweets of different sizes. Results: 87% (26) of children successfully learnt how to swallow pills after one training session (mean duration 14.5 min), and 92% (24) were discharged on pills. 75 prescribed oral liquid medications were deemed suitable for switching to pills. Of these, 89% (67) were switched successfully. Conclusion: Children as young as 3 years were successful in swallowing pills after training. Providing children PS training session within hospital is feasible and acceptable to children and their parents.